PENGEMBANGAN PENGETAHUAN TENTANG PAJAK PADA PENGUSAHA KECIL “JAMAICA FLOWERS” - Putri, Ayunda Tasya; Zainul, Muhsin; Derjualianda, Hifzan; Silmi, Silmi (Ensiklopedia Sosial Review, 2024)
Knowledge about taxation plays a crucial role in the success and compliance of small businesses, including the ornamental flower sector like Jamaika Flowers. This article explores efforts to develop tax knowledge in the context of small businesses, focusing on Jamaika Flowers, an ornamental flower business. The study aims to understand the taxation challenges faced by small businesses, analyze the effectiveness of tax education programs, and provide strategic recommendations to enhance tax understanding among ornamental flower entrepreneurs. This research employs a qualitative method with a case study approach, involving in-depth interviews with the owner of Jamaika Flowers, as well as a review of literature related to tax policies for small businesses in Indonesia. The results indicate that a lack of knowledge about tax obligations often becomes a major obstacle for small businesses in maintaining tax compliance. Factors such as the complexity of regulations, limited access to tax information, and resource constraints are significant issues.